Channel coordination on fixed-term maintenance outsourcing contracts. Issue 7 (2nd July 2016) - Pascual, Rodrigo; Santelices, Gabriel; Liao, Haitao; Maturana, Sergio
ABSTRACT: This article studies the positive and negative effects that fixed-term maintenance contracts may have on related decision-making. We present an original model to estimate such effects and select the optimal preventive maintenance intervals and contract terms for pieces of equipment that are serviced by an external party. In the context of the contract, the intention of each party is in general to maximize its own profit, which usually leads to unaligned interests and decisions. To resolve this issue, we propose incentive schemes to ensure the contract sustainability by achieving channel coordination between the client and its service vendor. Special focus is put on how the performed net-present-value analysis of both parties affects decision-making regarding equipment maintenance. Our model considers a new alternative of negotiating contracts with non-constant maintenance intervals. The proposed model helps to identify conditions that justify maintenance deferrals with their associated negligence, in terms of life cycle reduction and performance deterioration, when no channel coordination is promoted. Additionally, we present a simple procedure to settle an optimal contract duration, benefiting both parties. The proposed methodology is tested using a baseline case study from the literature. It illustrates how return-on-investment analysis may significantly impact optimal maintenance intervals during the contract for both parties. Accordingly, incentives need to be re-evaluated to achieve channel coordination. The suggested approach can be easily implemented in commercial spreadsheets, facilitating sensitivity analyses.